(untitled) (Global Journal of Human-Social Science, 2018)
No one can escape stress but we can learn to cope with it The work stress is found in all professions Military professionals are very stressed because they are highly target driven and highly pressured on results Military education and training is a process which intends to establish and improve the capabilities of military personnel in their respective roles Military profession by virtue of its inherent nature is full of stress where anxiety insecurity and uncertainty always prevail Military personnel are experiencing numerous type of stress based on situations like war time peace time and UN mission time Irrespective of officers and soldiers start their professional life through training in the academy where stresses are more intense So our writing will be focusing on those issues and try to draw a comprehensive guideline to enhance the performance of the military personnel by coping up with stress in adverse situations